Avaliação de um sistema de remoção de sólidos para maximização do uso da água no processamento dos frutos do cafeeiro - Moreli, Aldemar Polonini (2010)
Coffee is one of the most important activities in Brazil for it provides job opportunities to millions of people and contributes to keep people in the countryside. The Brazilian climate favors the production of fine coffees through both dry and wet proces